GAMBARAN PERAN PENGAWAS MINUM OBAT TENTANG PENGOBATAN TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS TAMBANG KECAMATAN TAMBANG KABUPATEN KAMPAR PROVINSI RIAU - Dwipa Dhurandhara; Suyanto "; Sri Melati Munir (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTTuberculosis ( TB ) is a contagious infectious disease that is a big cause of death. Case detection rate and cure rate of TB at the provincial level in Indonesia has yet to reach the global target. One component of TB DOTS namely the supervisors to take medication. Expected supervisors to take medication can function well in accordance with his duties as a PMO is to give a boost to the patient , remind patients to take medication , and sputum checked regularly. This type of research is descriptive qualitative approach with interviews and observations. Researcher get 12 samples from supervisors to take medication population who live at home with TB patients and patients with tuberculosis by using purposive sampling technique. Researchers also found that most of the supervisors to take medication for TB patients who are in the working area of the Tambang health center function well .Keywords:Supervisor to take medicaion, Treatment of tuberculosis, Tuberculosis